Assessment of cardiovascular risk factors among transgender population at Bhubaneswar, Odisha - Agarwal, Bhawna; Mandal, Arti Prabha (International Journal Of Community Medicine And Public Health, 2025)
Background: Cardiovascular disease (CVD) remains a leading cause of mortality worldwide, as reported by the WHO. In India, CVDs account for 28.1% of total deaths and 14.1% of all disability-adjusted life years (DALYs). However, existing evidence predominantly focuses on cisgender populations, overlooking sexual and gender minorities such as transgender women, who face unique health vulnerabilities due to social exclusion, stigma, and limited healthcare access. This study aims to assess the prevalence of cardiovascular risk factors among transgender women in Bhubaneswar, Odisha. Methods: A cross-sectional descriptive study was conducted using simple random sampling among transgender individuals aged 18 years and above. A sample size of 196 was calculated using OpenEpi. Data were collected through structured interviews and analyzed using SPSS software. Results: Results revealed that 50.3% of the participants abstained from alcohol, while the rest reported regular consumption. Poor dietary patterns were observed, with 45.2% reporting no fruit intake and 1.7% reporting no vegetable intake in the previous week. Physical inactivity was high, with 35.6% not engaging in moderate-intensity activity and 81.4% in vigorous activity. Over half of the participants were in the high CVD risk category, with 19.8% overweight, 29.4% classified as obesity class I, and 7.9% as obesity class II. Hypertension was present in 22.6% of the population, and notably, 40% of those aged 18-28 years were hypertensive. Other reported conditions included diabetes (6.8%), high cholesterol (2.3%), HIV/AIDS (5.6%), and neurological disorders (1.1%). Conclusions: The mean age of participants was 28.3 years (SD=7.7), indicating early emergence of CVD risk factors in this marginalized group.